Study of Gastropods and Bivalves Potential in Mangrove Ecosystem in Sebubus , Paloh - Nur Istiqamah; Angga Tritisari; Uray Januardy (Berkala Perikanan Terubuk, 2021)
This study aims to obtain data on the abundance of gastropods and bivalves, the density, and the diversity in the mangrove ecosystem in Sebubus Village, Paloh District. The data obtained from this study shed a light in the management of aquatic ecosystems as well as the reference in conserving and identifying mollusks with economic value. Observations from 20 stations revealed that the number of gastropod populations was higher than the population of bivalves. Gastropod abundance was mostly found in Padak and bivalves was mostly found in Engkalan A. Thus, it is necessary to provide information regarding the fishing limits around the mangrove forest o the community. It is necessary to establish a an asylum for gastropods and bivalves as well as support for their sustainability